2015
DOI: 10.1016/j.btre.2015.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of tannase production by a novel Klebsiella pneumoniae KP715242 using central composite design

Abstract: A novel tannase producing bacterial strain was isolated from rhizospheric soil of Acacia species and identified as Klebsiella pneumoniae KP715242. A 3.25-fold increase in tannase production was achieved upon optimization with central composite design using response surface methodology. Four variables namely pH, temperature, incubation period, and agitation speed were used to optimize significant correlation between the effects of these variables on tannase production. A second-order polynomial was fitted to da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…The yeast isolation and screening were performed as previously reported [21]. As for the screening of tannin-utilizing yeast strains, the visual reading method was executed according to Kumar, with some modifications [22]. A single yeast colony was picked and inoculated the plate of the test medium at 28 °C for 3 days, then green to brown coloration of the medium was judged as a positive result for tannin degradation.…”
Section: Methodsmentioning
confidence: 99%
“…The yeast isolation and screening were performed as previously reported [21]. As for the screening of tannin-utilizing yeast strains, the visual reading method was executed according to Kumar, with some modifications [22]. A single yeast colony was picked and inoculated the plate of the test medium at 28 °C for 3 days, then green to brown coloration of the medium was judged as a positive result for tannin degradation.…”
Section: Methodsmentioning
confidence: 99%
“…They contain the bacteria: Bacillus sp. PAB2, B. licheniformis KBR6 and Klebsiella pneumoniae KP715242 (Jana et al, 2012 andKumar et al, 2015); yeast: Kluyveromyces marxianus NRRL Y-8281 and Saccharomyces cerevisiae CCMB 520 (Fathy et al, 2017 andMorgana de Melo Lopes et al, 2017) and fungi:…”
Section: Introductionmentioning
confidence: 99%
“…whereas tannase activity pH optima for Bacillus cereus KBR9 and Bacillus licheniformis KBR 6 was 4.5 and pH 5.75 respectively (Mondal and Pati 2000;Rodríguez et al 2008). Several other investigators have reported the optimal pH from 4 to 5 (Gayen and Ghosh 2013;Bagga et al 2015;Kumar et al 2015;Farag et al 2018). However, some reports also indicated the activity in alkaline range (Iwamoto et al 2008).…”
Section: Discussionmentioning
confidence: 99%